Assessing the impact of gout on cancer risk and the role of healthy lifestyles - Shi, Wenru; Zhang, Jie; Wei, Sitong; Wang, Xiang; Cao, Hongfei; Ye, Dongqing; Fang, Xinyu (Frontiers in Oncology, 2025)
BackgroundConflicting evidence exists on the link between gout and cancer risk, with limited clarity on the impact of healthy lifestyle factors.MethodsIn the UK Biobank, 7,169 gout patients were matched with 21,507 non-gout controls (1:3 ratio) using propensity scores. Cox regression models assessed cancer risk associated with gout. Among 6,105 gout patients, cancer risk was further evaluated using an eight-factor Healthy Lifestyle Score (HLS) and a weighted HLS.ResultsGout was linked to a higher cancer incidence [HR (95% CI) = 1.075 (1.013-1.140)]. High HLS in gout patients correlated with a lower cancer risk [HR (95% CI) = 0.825 (0.717-0.948)], with the strongest protective effect observed in those aged ≥60. Sensitivity analyses confirmed these findings.ConclusionGout patients have a higher risk of developing cancer, but a healthy lifestyle, particularly in those aged 60 and older, significantly reduces this risk. These findings highlight the importance of lifestyle interventions for cancer prevention in patients with gout.